Sosialisasi pemanfaatan google sites sebagai portal pembelajaran berbasis teknologi bagi guru PAUD - Windarsih, Chandra Asri; Wulansuci, Ghina; Alam, Syah Khalif; Lestari, Ririn Hunafa; Trisniarti, Susanti (IKIP SILIWANGI, 2025)
The low utilization of information and communication technology (ICT) by early childhood (PAUD) teachers in developing competencies, along with their lack of motivation to use ICT as a teaching aid, are among the challenges of 21st-century education in PAUD institutions. One of the technological tools that can be utilized is Google Sites, which serves as a learning portal. The purpose of this community service activity is to promote the use of Google Sites as a technology-based learning portal for early childhood education. This activity was designed using the Participatory Action Research (PAR) approach, consisting of the stages to know, to understand, to plan, to act, and to change. Based on the planning of the community service activity, the results indicate that one of the essential competencies of PAUD teachers—namely pedagogical competence—requires them to select and utilize ICT in both learning and administrative management. Accordingly, the technological tool is one component of Google Workspace, specifically Google Sites. Google Sites can be an alternative solution for teachers to present learning components in website format, as it allows easy and free access to website creation and development. Rendahnya pemanfaatan teknologi informasi dan komunikasi oleh guru PAUD dalam mengembangkan kompetensi serta kurangnya motivasi guru dalam menggunakan TIK sebagai alat bantu mengajar menjadi isu pendidikan abad 21 di satuan PAUD. Oleh karena itu salah satu perangkat teknologi yang dapat digunakan adalah google sites sebagai portal pembelajaran. Maka dari itu tujuan dari pengabdian ini adalah untuk mensosialisasikan pemanfaatan google sites sebagai portal pembelajaran anak usia dini berbasis teknologi. Kegiatan ini direncanakan menggunakan desain Participatory Action Research (PAR) yang terdiri dari tahapan to know, to understand, to plan, to action dan to change. Berdasarkan perencanaan kegiatan pengabdian diperoleh hasil bahwa salah satu kompetensi guru PAUD yaitu kompetensi pedagogik yang menuntut guru untuk memilih dan memanfaatkan teknologi informasi dan komunikasi dalam pembelajaran dan pengelolaan administrasi. Oleh karena itu perangkat teknologi yang diperkenalkan adalah salah satu ragam jenis dari google workspace yaitu google sites. Google sites dapat menjadi solusi alternatif guru dalam menyediakan komponen pembelajaran dalam bentuk tampilan website, dikarenakan kemudahan dalam mengakses dan mengembangkan tampilan website dengan gratis.